Acute effects of dynamic and pnf stretching on leg and vertical stiffness on female gymnasts - Dallas, G.; Pappas, P.; Dallas, C.; Paradisis, G. (Science of Gymnastics Journal, 2021)
The purpose of the study was to investigate the acute effect of Dynamic (DS) and PNF stretching on leg (Kleg) and vertical stiffness (Kvert) on female gymnasts. Thirty-one female athletes from various types of gymnastics (artistic, rhythmic, team gymnastics) participated in this study ([Mean ± SD] age: 22.32 ± 3.35 years, height: 164.87 ± 4.96 cm, body mass: 57.20 ± 6.54 kg) performed 30 sec running bouts at 4.44 m *s-1, under 3 different stretching protocols (PNF, DS, and no stretching [NS]). The total duration in each stretching condition was 6 minutes, and each of the 4 muscle groups was stretched for 40 seconds. Leg and vertical stiffness values were calculated using the "sine wave" method. No significant influence of stretching type on Kleg and Kvert were found after DS and PNF stretching. However, significant changes were found in Fmax, Dy, flight time (tf), step rate (SR), and step length (SL) after DS and PNF stretching protocol, indicating that DS produced greater changes compared to PNF protocol.